Pembiasaan Khataman Al-Qur’an Untuk Meningkatkan Semangat Mengaji Santri Di Madin Manba’ul ’Ulum Dukuh Sekuwung Sukorejo Ponorogo - Ahmad Mustaghfirin; Maulida Agustina Hidayatul Wahidah; Arik Dwijayanto (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Madrasah Diniyah Manba' ul 'Ulum was founded in 2008 in Sekuwung hamlet and is one of the educational institutions that studies religious sciences which aims to provide students with experience, knowledge, prayer skills and good attitudes in participating in Islamic religious and social education. This is considered important because reciting the Koran or reading the Al-Qur'an is knowledge for students that has become part of their studies and reciting the Al-Qur'an is a form of worship that has great rewards. This research uses a qualitative descriptive method with observation and interview data collection techniques with ustad and ustazah about how the habit of reciting the Al-Qur'an increases the enthusiasm of students to recite the Koran. The obstacle in the Koran recitation process is that they are not yet fluent in pronouncing the hijaiyah letters and also the students' knowledge of the contents of the Al-Qur'an. This decline occurred due to the negative impact of technology, especially on smartphones, which greatly influenced students' interest in reciting the Koran and students' lack of knowledge in understanding the Al-Qur'an. The results of this research state that the habit of reciting the Al-Qur'an can increase students' interest in reciting the Koran with evidence that reciting the Al-Qur'an has a good impact on students, improves the ability to read the Al-Qur'an, especially the makhorijul letters and recitation, and can Cultivate students with good morals.